Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/jsfa.8452
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of beehive products as ingredients in quinoa bars

Abstract: BACKGROUND: The aim of this work was to develop a puffed quinoa bar with beehive products of high content of phenolic compounds, based on acceptability and perception of consumers. A rotational central composite design of three variables (honey, pollen and propolis) was used for food product formulation. The responses to optimize were sensorial acceptability and polyphenol content. Next to acceptability a check-all-that-apply (CATA) test was performed with 115 consumers. Preference maps were used to relate acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
0
6
0
6
Order By: Relevance
“…The panelists were grouped in three groups (G1, G2, and G3) in all tasted meat products, except for pork liver pâté where they were grouped in four groups (G1, G2, G3, and G4). Research carried out by Rios, Lobo, and Samman () also showed that the incorporation of beehive products in quinoa bars generated consumers groups with different acceptability profiles.…”
Section: Resultsmentioning
confidence: 98%
“…The panelists were grouped in three groups (G1, G2, and G3) in all tasted meat products, except for pork liver pâté where they were grouped in four groups (G1, G2, G3, and G4). Research carried out by Rios, Lobo, and Samman () also showed that the incorporation of beehive products in quinoa bars generated consumers groups with different acceptability profiles.…”
Section: Resultsmentioning
confidence: 98%
“…The fresh samples were presented to consumers in a plate with samples of about 10 g each. The test was completed by adults, with CATA (check-allthat-apply) questions 19 . For this purpose, a list of 25 terms was presented to the consumers asking them to mark all the ones they considered appropriate to describe the product.…”
Section: Preparation Of Bakery Productmentioning
confidence: 99%
“…Frente a este problema, se hace necesario modificar los hábitos alimentarios en las personas, promocionando el aumento de actividad física y alimentación saludable consumiendo frutas, cereales, alimentos con bajo contenido de azúcar y alto aporte de fibra dietética para inducir mayor saciedad [3,4]. En los últimos años, la demanda y el consumo de alimentos que contienen nutrientes y otros compuestos con propiedades beneficiosas para la salud han aumentado rápidamente; estos son conocidos como alimentos funcionales [5]. Actualmente, los consumidores prefieren alimentos en los cuales se perciba propiedades de salud y, al mismo tiempo, convenientes para un fácil consumo, almacenamiento y manipulación.…”
Section: Introductionunclassified
“…Ingredientes usualmente contenidos en barras de cereales son mezclas de cereales (trigo, maíz, avena, arroz), frutas secas y nueces, jarabe de maíz, miel, azúcar, lecitina y saborizantes. Por lo tanto, es posible obtener este tipo de producto con mayor calidad nutricional y funcional eligiendo y complementando las materias constituyendo una opción de comida con beneficios [5,7,8].…”
Section: Introductionunclassified
See 1 more Smart Citation